2016
DOI: 10.1016/j.optcom.2015.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Modal analysis of the impact of the boundaries on transverse Anderson localization in a one-dimensional disordered optical lattice

Abstract: Impact of the boundaries on transversely localized modes of a truncated one-dimensional disordered optical lattice is numerically studied. The results show lower modal number density near the boundaries compared with the bulk, while the average decay rate of the tail of localized modes is the same near the boundaries as in the bulk. It is suggested that the perceived suppressed localization near the boundaries is due to a lower mode density: on average, it is less probable to excite a localized mode near the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The MA-PDF encompasses all the relevant statistical information on TAL; it relies solely on the physics of the disordered system and the physical nature of the propagating wave, and is independent of the beam properties of the external excitation. It also makes the TAL behavior very transparent to the observer, where one can clearly differentiate between the localized and extended modes [30,31]. As such, one can strategize the optimization of the waveguide using desired objective functions.…”
mentioning
confidence: 99%
“…The MA-PDF encompasses all the relevant statistical information on TAL; it relies solely on the physics of the disordered system and the physical nature of the propagating wave, and is independent of the beam properties of the external excitation. It also makes the TAL behavior very transparent to the observer, where one can clearly differentiate between the localized and extended modes [30,31]. As such, one can strategize the optimization of the waveguide using desired objective functions.…”
mentioning
confidence: 99%
“…This caused a bit of debate, considering the perceived delocalizing impact of the boundaries in disordered TAL systems [47], [55]- [57], which was subsequently addressed in Ref. [58], as will be discussed in more detail in subsection III-B. In 2014, there was another successful attempt in observing TAL in an air-glass optical fiber by Chen and Li [59] at Corning Incorporated.…”
Section: Tal In Disordered Optical Fibersmentioning
confidence: 99%
“…However, Abaie et al later performed a detailed analysis in Ref. [58] and showed that the perceived suppressed localization near the boundaries is due to a lower mode density near the boundaries compared with the bulk, while the average decay rate of the tail of localized modes is the same near the boundaries as in bulk. Therefore, on average, it is less probable to excite a localized mode near the boundaries; however, once it is excited, its localization is with the same exponential decay rate as any other localized mode.…”
Section: B Tal Near the Disordered Fiber Boundariesmentioning
confidence: 99%
“…Transverse Anderson localization (TAL) [5][6][7][8][9] has recently fostered a new class of disordered waveguides, in which strong transverse confinement mediated by Anderson-localized modes balances the diffraction of light as it propagates freely along the waveguide [10][11][12][13]. In a recent study, it has been shown that localized modes of a disordered fiber can be exploited for singlemode transmission [14].…”
mentioning
confidence: 99%